Analysis of Psychosocial Factors Affecting Dietary Behavior among People with Type 2 Diabetes Mellitus in Indonesia - Rondhianto, Rondhianto; Ridla, Akhmad Zainur; Kurniawan Setia Budi, Fandi Ahmad (Fakultas Ilmu-ilmu Kesehatan, 2023)
Dietary behavior is essential to diabetes self-management in people with type 2 diabetes mellitus. Understanding factors influencing diabetes self-management will help in designing appropriate intervention. The study aims to determine the effect of psychosocial on dietary behavior. This study was an analytical observational with a cross-sectional design. The sample size was 138 respondents recruited with multistage random sampling. Psychosocial factors were identified using; 1) Spoken Knowledge in Low Literacy patients with Diabetes Scale, 2) The Coping Scale, 3) Diabetes Distress Scale, 4) Hensarling Diabetes Family Support Scale, 5) Perceived nurse support questionnaire, while dietery behaviour was measured by Self-Management Dietary Behaviors Questionnaire. Data analysis used multiple linear regression. Among five psychosocial factors only two factors influenced dietary behaviour, such as; distress and perceived family support (p=0.004; p=0.001 < α=0.05). Meanwhile, knowledge, coping, and perceived nurse support did not affect diabetes diet (p=0.133; p=0.527; p=0.535 > α=0.05) with R2 = 0.275 (F=11.148; p=0.001 <α=0.05). Distress and perceived family support are two psychosocial factors that can affect dietary behavior. Preventing the occurrence of distress and increasing family support are important to improve dietary behavior adherence in people with type 2 diabetes mellitus.